Numerical analysis of collision mechanism that causes particle tribocharging in dry powder inhaler - Ryosuke Mitani; Muhammad Aiman bin Mohd Nor; Takuto Iinuma; Tatsuhiro Mori; Tomoaki Okuda (Asian Journal of Atmospheric Environment)
Abstract Chronic obstructive pulmonary disease (COPD) is induced by inhalation of toxic substances such as cigarettes and air pollution. Dry powder inhalers (DPIs) are the primary treatment for these diseases. However, they have some problems, such as residuals in a capsule caused by electrostatic force before reaching the human lungs. This study investigated the particle tribocharging mechanism in a DPI using a tandem differential mobility analyzer (TDMA) and a combined discrete element method and computational fluid dynamics (DEM-CFD) approach. In the TDMA experiment, the charging state of the particles changed from negative to positive charge in the DPI device fabricated by the 3D printer. This is because tribocharging is caused by particle–particle collisions and particle–wall collisions. In the numerical simulation, particle–wall collisions occurred more frequently than particle–particle collisions. Therefore, the particle–wall collisions change the charging state of the particle in the DPI device. These results suggest that collisions between particles and walls of the device cause the particles to become charged, leading to a decrease in their deposition in the deeper regions of the lungs. Moreover, the large turbulence kinetic energy of the airflow in the DPI device caused particle–wall collisions because the particles were widely dispersed in the DPI device. These results suggest that optimum turbulence kinetic energy is necessary to reduce particle aggregation and improve the delivery efficiency of DPIs to the human lungs. Graphical Abstract